An approach of web stiffener calculation in thin-walled columns - Stulpinas, Mantas; Daniūnas, Alfonsas (Journal of Civil Engineering and Management, 2024)
This article presents an analytical approach for calculating web stiffeners in thin-walled columns. A novel method is introduced, which treats each bending point in the cross-section web as a separate stiffener. The advantages of this calculation method are discussed, highlighting its increased versatility in designing cross-section geometry. The load-bearing strength of axially compressed thin-walled closed cross-section columns, calculated using this method, is compared to analytical calculations based on the Eurocode 3-1-3 methodology and to the finite element method analysis. Calculation results of columns with cross-sections including shallow web stiffeners were up to 9.22% less conservative when compared to the Eurocode 3-1-3 methodology. The results demonstrate great compliance of the proposed method for column crosssections with deep stiffeners. Finite element method (FEM) analysis was performed to verify the calculated load bearing strengths of the columns according to both calculation methodologies. FEM analysis confirmed the reliance of the calculated results and showed, that the load bearing strengths calculated using the newly presented methodology were ranging from 88.77% to 97.86% of load bearing strength calculated using finite element method. These results proved, that the proposed method provides an accurate load bearing strength of thin-walled columns with web stiffeners.